PENGARUH TERAPI RELAKSASI BENSON TERHADAP TEKANAN DARAH LANSIA HIPERTENSI DI PANTI SOSIAL TRESNA WERDHA - la rangki (Universitas 'Aisyiyah Bandung, 2020)
Benson relaxation therapy to be used alternative therapy to normalize blood pressure. The aim of this study was to determine the effect of benson relaxation therapy on blood pressure in eldery hypertension and to know the difference in blood pressure between the intervention group and the control group at Social Institution of Tresna Werdha Minaula Kendari. This study used the Quasi experimental pre-post test with control group.The sampling techique used  total sampling with 14 respondents. Data analysis used paired T-test to test one group in the intervention and control group and Mann Whitney test to see differences between the two groups ( p = < 0,05). The results showed a significant effect of benson relaxation therapy on stystolic and diastolic blood pressure in the intervention group (p  = 0,000 for systolic and p = 0,004 for diastolic). ). Whereas in the control group there  was no change in systolic blood pressure ( p = 0,069 for systolic and diastolic show blood pressure p = 0,016).